Hak Menerima Dan Menolak Vaksin Sinovac Ditinjau Dari Hak Asasi Manusia Dan Fiqih Siyasah (Studi Kasus Di Puskesmas Gantar) - Azis Rijal Muklis; Siti Ngainnur Rohmah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
The national vaccination program (Sinovac vaccine), which is intended for all Indonesian people, is one of the government's efforts to control the spread of the corona virus (covid-19). So to guarantee the rights of the people in receiving the vaccine, it is necessary to have an in-depth study of the program in terms of human rights and fiqh siyasa in order to prevent abuse of rights for all Indonesian people. This study aims to determine the right to receive and refuse the sinovac vaccine according to human rights and fiqh siyasah and to determine the implementation of the use of the right to receive and refuse the sinovac vaccine according to human rights and fiqh siyasah. The method used in this study is qualitative with a literature and empirical approach. The results of the study show that according to human rights, accepting and rejecting the Sinovac vaccine is flexible, people can still consciously choose whether they want to be vaccinated or not, because there are no criminal provisions that regulate sanctions for civil society if they do not get vaccinated. Meanwhile, according to siyasa fiqh, although the legal origin of vaccination is allowed, its legal status can change based on the reasons and conditions. The law can be mandatory, sunnah, haram and makruh according to the reasons and conditions.Keywords: Sinovac Vaccine; Human rights; Fiqh Siyasah AbstrakProgram vaksinasi nasional (vaksin Sinovac) yang ditunjukan untuk seluruh masyarakat Indonesia, menjadi salah satu upaya pemerintah dalam pengendalian penyebaran virus corona (covid-19). Maka untuk menjamin hak-hak masyarakat dalam penerimaan vaksin tersebut, perlu adanya kajian yang mendalam mengenai program tersebut dari segi hak asasi manusia serta fiqih siyasah guna mencegah terjadi penyelewengan hak bagi seluruh masyarakat Indonesia. Penelitian ini bertujuan untuk mengetahui hak menerima dan hak menolak vaksin sinovac menurut hak asasi manusia dan fiqih siyasah serta untuk mengetahui pelaksanaan penggunaan hak menerima dan hak menolak vaksin sinovac menurut hak asasi manusia dan fiqih siyasah. Metode yang digunakan dalam penelitian ini adalah kualitatif dengan pendekatan literatur dan empiris. Hasil penelitian menunjukan bahwa menurut hak asasi manusia, menerima dan menolak vaksin sinovac hukumnya fleksibel, masyarakat masih bisa memilih secara sadar ingin divaksin atau tidak, karena belum ada ketentuan pidana yang mengatur sanksi bagi masyarakat sipil bila tidak vaksin. Adapun menurut fiqih siyasah meski asal hukum vaksinasi diperbolehkan, status hukumnya bisa berubah berdasarkan alasan dan kondisinya. Hukumnya bisa menjadi wajib, sunah, haram dan makruh sesuai dengan alasan dan kondisinya.Kata Kunci: Vaksin Sinovac; Hak Asasi Manusia; Fiqih Siyasah